2012
DOI: 10.1371/journal.pone.0033270
|View full text |Cite
|
Sign up to set email alerts
|

Infection-Associated Nuclear Degeneration in the Rice Blast Fungus Magnaporthe oryzae Requires Non-Selective Macro-Autophagy

Abstract: BackgroundThe rice blast fungus Magnaporthe oryzae elaborates a specialized infection structure called an appressorium to breach the rice leaf surface and gain access to plant tissue. Appressorium development is controlled by cell cycle progression, and a single round of nuclear division occurs prior to appressorium formation. Mitosis is always followed by programmed cell death of the spore from which the appressorium develops. Nuclear degeneration in the spore is known to be essential for plant infection, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…In contrast to PMN, nuclear degradation in M. oryzae is dependent on core autophagy genes, such as M. oryzae ATG1 or ATG4 (Kershaw and Talbot, 2009). In contrast to large ring-like autophagosomes that mediate the degradation of A. oryzae nuclei, only smaller, more punctate autophagosomes surround the target nucleus during appressorium formation in M. oryzae (He et al, 2012). Moreover, the nucleus does not appear to be fully degraded, suggesting that nuclear breakdown might be performed by distinct macroautophagy-dependent processes in filamentous fungi (He et al, 2012).…”
Section: Macroautophagy-mediated Degradation Of Entire Nuclei In Filamentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast to PMN, nuclear degradation in M. oryzae is dependent on core autophagy genes, such as M. oryzae ATG1 or ATG4 (Kershaw and Talbot, 2009). In contrast to large ring-like autophagosomes that mediate the degradation of A. oryzae nuclei, only smaller, more punctate autophagosomes surround the target nucleus during appressorium formation in M. oryzae (He et al, 2012). Moreover, the nucleus does not appear to be fully degraded, suggesting that nuclear breakdown might be performed by distinct macroautophagy-dependent processes in filamentous fungi (He et al, 2012).…”
Section: Macroautophagy-mediated Degradation Of Entire Nuclei In Filamentioning
confidence: 96%
“…To be able to infect rice plants, M. oryzae forms a specialized structure, the appressorium, which generates immense intracellular turgor pressure that results in the direct rupture of the plant cuticle and, thereby, facilitates fungal entry and colonization of plant tissue . Appressorium development involves a number of steps, one of which is nuclear degeneration in the spore from which the appressorium develops (see Poster) (Veneault-Fourrey et al, 2006;He et al, 2012). Although, M. oryzae possesses homologs of Vac8 and Tsc13, components of a putative PMN pathway, an Nvj1 homolog has not been identified and there is no evidence for the formation of NV junctions and for PMN activity.…”
Section: Macroautophagy-mediated Degradation Of Entire Nuclei In Filamentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it was reported that nucleophagy of a whole nucleus occurs during appressorium formation required for plant infection in the rice blast fungus Magnaporthe oryzae (He et al, 2012) and after vegetative cell fusion and during nitrogen starvation in another plant pathogen Fusarium oxysporum (Corral-Ramos et al, 2015). In A. oryzae, the morphological process of nucleophagy has been characterized by fluorescence microscopy under the expression of an enhanced green fluorescence protein (EGFP)-fused AoAtg8, an orthologue of the autophagsomal marker S. cerevisiae Atg8, (EGFP-AoAtg8) and the nuclear marker mDsRed-fused histone H2B (H2B-mDsRed) (Shoji et al, 2010); AoAtg8-positive crescent-and cup-shaped autophagosome precursors are formed in the vicinity of the mDsRed-labeled nucleus, and then a ring-like autophagosome engulfs the whole nucleus.…”
Section: Introductionmentioning
confidence: 99%